2015
DOI: 10.4103/0366-6999.150089
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Brain Glucose Metabolism Changes in Patients with Lung Cancer of Different Histological Types

Abstract: Background:Cerebral glucose metabolism changes are always observed in patients suffering from malignant tumors. This preliminary study aimed to investigate the brain glucose metabolism changes in patients with lung cancer of different histological types.Methods:One hundred and twenty patients with primary untreated lung cancer, who visited People's Hospital of Zhengzhou University from February 2012 to July 2013, were divided into three groups based on histological types confirmed by biopsy or surgical patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…In this study, no significant differences were found in brain glucose uptake among clinical stages or between adenocarcinoma and squamous carcinoma patients. These results were partly in line with the study of Li and colleagues [ 31 ]. However, the effect of clinical stages or pathological types on brain glucose uptake might be related to the whole-body tumor burden.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, no significant differences were found in brain glucose uptake among clinical stages or between adenocarcinoma and squamous carcinoma patients. These results were partly in line with the study of Li and colleagues [ 31 ]. However, the effect of clinical stages or pathological types on brain glucose uptake might be related to the whole-body tumor burden.…”
Section: Discussionsupporting
confidence: 92%
“…2,5,18,[23][24][25] Decreased cerebral blood flow, decreased metabolism, 1,2 and reduction of gray matter volume 26,27 in the PFC, OFC, and anterior cingulate cortex were also observed in depressive patients. Notably, these changes were proportional to depression severity 26 and could be partly recovered with attenuation of psychiatric symptoms 1,17,28 due to an effective therapeutic response. 2,29…”
Section: Discussionmentioning
confidence: 99%
“…It was reported associated with depression and chemobrain, 30 and such cerebral metabolism could see in Alzheimer’s disease too. 1 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations